A Multivalent Probe for AI-2 Quorum Sensing Receptors - Garner, Amanda L. (2011)
Multivalency is a common principle in the recognition of cellular receptors, and multivalent agonists and antagonists have played a major role in understanding mammalian cell receptor biology. The study of bacterial cell receptors using similar approaches, however, has lagged behind. Herein we describe our efforts toward the development of a dendrimer-based multivalent probe for studying AI-2 quorum sensing receptors. From these studies, we have discovered a chemical probe specific for Lsr-type AI-2 quorum sensing receptors with the potential for enabling the identification of new bacterial species that utilize AI-2 as a quorum sensing signaling molecule.